The Animalistic Mosaics in Early Christian Macedonia - Obraztsova, Ksenia B. (Actual Problems of Theory and History of Art, 2021)
The article is dedicated to zoomorphic motifs in the Early Christian floor mosaics of the 4th–6th centuries in Macedonia. The paper involves a survey of common compositional schemes and separate elements of the animalistic mosaics, where the ensembles of Macedonia are set in a broad context of the Late Antique art. While reviewing the repertory of the zoomorphic motifs, we pursued two main goals. First, to observe the regional specificity of the Macedonian monuments. Second, to examine from them the general attitudes of the period towards artistic and symbolic interpretation of the animalistic patterns.Some compositional types had been rooted especially deeply in the area; however, they find numerous analogies among both the neighbouring and quite distant regions. We suggest that the most zoomorphic patterns, particularly the narrative depictions such as chase or combat of animals, maintained the neutral meaning in the Christian context. They had been barely transformed into symbolic images, but kept functioning as large-scale elements of decoration, defined rather by the aesthetic principles than the theological thought of the epoch.This research has been completed with support of the Russian Science Foundation (RSF), project № 20-18-00294.
Keywords: Early Christian art; Late Antique art; Macedonia; zoomorphic motifs; floor mosaics